Employing the Beamforming Technique to Enhance the Medical Ambulance Performance, IoMT - Mushtaq Al-Sharify; Talib A. Al-Sharify; Noor T. Al-Sharify; Zainab T. Al-Sharify; Ashwaq T. Al-Sharify; Mustafa Akeel Kareem; Aymen Mohammed Khodayer Al-Dlaimi (Tikrit Journal of Engineering Sciences)
The radio frequency signal is important for improving the connection among patients, hospitals, and healthcare ambulances. Emergency specialists significantly monitored global healthcare in real-life conditions during the previous century, depending on telecommunications. 5G mobile telecommunication networks have increased smart navigation with 3D dimensions' position for drones, unmanned aerial vehicles, and ambulance vehicles. Ambulances equipped with the Internet of Medical Things (IoMT) enabled smart antennas are the subject of this research. The article's objective is to improve the performance of medical ambulances in real-time and safe health zones by employing the beamforming technique of 5G with advanced MIMO technologies and using vehicles for everything (V2X). Critical components like patient care, delay, and road traffic are analyzed and considered for various smart connections between ambulances and patients to hospitals. The results will help reduce the time delay in transferring data to healthcare systems, which profoundly impacts transferring patient care data faster, enabling healthcare providers to access medical information about the patient. Simulations are used to confirm theoretical results.